Community-Based Drug Rehabilitation and Care in Philippine Local Governments - Hechanova, Ma. Regina (Archīum Ateneo, 2022)
This research examined the enablers, barriers, and outcomes of community-based drug rehabilitation programs in Philippine local governments. A multicase study research design was used in collecting and analyzing narratives from 38 leaders, program implementers, and participants in five local government units that implemented community-based drug rehabilitation. Using the World Health Organization’s Health Systems framework, the study elicited barriers and enablers in terms of leadership, financing and access to resources, information system, workforce, and service delivery. Beyond these, a unique theme that emerged was the salience of context and culture, specifically, the influence of poverty, community, and stigma. Despite these challenges, clients, providers, and leaders report positive outcomes including improved health and well-being, social/ financial protection for the clients, and access to services. The implications of findings on policy and practice are discussed.